Reflectivity measurement of a silicon carbide mirror sample for ITER divertor vacuum ultraviolet spectrometer - Kim, Yoo Kwan; Seon, Changrae; An, Younghwa; Hong, Joohwan; Cheon, Munseong; Kim, Boseong; Kim, Yu Kwon (Review of Scientific Instruments, 2024)
The first mirror is the front-end optic component that reflects light emitted from the plasma to the diagnostic system in fusion plasmas. Silicon carbide (SiC), known for its relatively high mechanical strength and radiation tolerance, has been selected as the substrate material for the first mirror in the ITER divertor vacuum ultraviolet (VUV) spectrometer. To measure the reflectivity of the ellipse cylindrical SiC mirror to be manufactured, a device for reflectivity measurement in the VUV wavelength range was developed. First, the reflectivity of a sample SiC mirror (15 mm diameter × 10 mm thick) was measured across the ITER-required incidence angles, and the results are reported in this study. A hollow cathode lamp with helium gas was used as the VUV light source in the wavelength range of 23-60 nm, and a dedicated VUV spectrometer to select specific wavelengths was developed. The spectrometer utilized laminar-type replica diffraction gratings (Shimadzu 30-006) and two back-illuminated charge-coupled devices (BI-CCD, Andor DO 940P-BEN) for the grating and detector, respectively. A cropping technique with aperture was employed to precisely localize the VUV light’s reflection onto the SiC mirror surface. The experimentally measured reflectivity values of SiC at the required incidence angles of VUV light were compared with theoretically calculated reflectivity curves. The oxidation layer (SiO2) formed on the SiC surface and the incidence angle of VUV light to the BI-CCD chip (E2V) would be the factors affecting the accuracy of the reflectivity.
Keywords: Diagnostic systems; First mirror; Front end; Incidence angles; ITER divertor; Measurements of; Reflectivity measurements; Vacuum ultraviolet Light; Vacuum ultraviolets; Wavelength ranges